Platelet-derived growth factor A mRNA in platelets is associated with the degree of hepatic fibrosis in chronic hepatitis C - Tanikawa, Aline Aki [UNESP]; Tommasini Grotto, Rejane Maria [UNESP]; Silva, Giovanni Faria [UNESP]; Ferrasi, Adriana Camargo [UNESP]; Rodrigues Sarnighausen, Valeria Cristina [UNESP]; Moura Campos Pardini, Maria Ines de [UNESP] (Soc Brasileira Medicina Tropical, 2017)
Introduction: Transforming growth factor beta 1 (TGFB1) and platelet-derived growth factor (PDGF) are the main cytokines related to hepatic fibrogenesis. Methods: RNA isolated from the platelets and hepatic tissue of 43 HCV carriers was used for quantitative polymerase chain reaction to determine TGFB1, PDGFA, and PDGFB RNA expression. Results: The mRNA expression of PDGFA in platelets was significantly lower in the group with advanced fibrosis than in the group with early-stage fibrosis. TGFB1 was more frequently expressed in platelets than in hepatic tissue, which was different from PDGFB. Conclusions: A pathway mediated by overexpression of TGFB1 via PDGFA in megakaryocytes could be involved in the development of fibrosis.
Keywords: Hepatic fibrosis; PDGF; TGFB